Periodontitisli hastalarda ortodontik tedavi - ACAR, YASEMİN BAHAR (Türkiye Klinikleri, 2021)
Toplumda ortodontik tedavinin sadece çocukluk ve ergenlik döneminde değil, her yaştaki bireyde uygulanabileceğine dair farkındalığın artmasıyla birlikte tedavi için kliniklere başvuran erişkin hastaların sayısı giderek artmaktadır. Bu erişkin hastaların arasında farklı şiddette ve yaygınlıkta periodontitise sahip olgular da yer almaktadır. Periodontitisli hastalarda ortodontik tedavinin hedefi hastanın birincil şikayeti olan estetik görünümün düzeltilmesinin yanı sıra hastanın periodontal sağlığının idame ettirilebilmesi ve gerekiyorsa protetik rehabilitasyona kolaylık sağlayacak bir diş dizilimi ve oklüzyonun tesis edilmesidir. Ortodontik tedavi öncesinde, sırasında ve sonrasında gerekli tedbirlerin alınması koşuluyla ve ortodontist, periodontist ve hasta işbirliği ile başarılı sonuçlar elde etmek mümkündür.

Along with the increasing awareness about orthodontic treatment not being specific to childhood and adolescence, and malocclusions can also be treated in adulthood, the number of adult patients seeking orthodontic treatment have increased. Some of these patients may have periodontal problems of varying severity. Aims of orthodontic therapy in periodontally compromised patients include not only the esthetic correction, which is usually the primary concern of the patient, but also to establish an occlusion that will help to maintain periodontally healthy tissues and prepare a base for the necessary prosthetic rehabilitation. By taking the necessary precautions prior to, during, and after the orthodontic treatment and with cooperation between the orthodontist, periodontist and the patient, successful treatments will be possible.
Orthodontic treatment in patients with periodontitis
Keywords: Kronik periodontitis; ortodonti; düzeltici; erişkin; Chronic periodontitis; orthodontics; corrective; adult